Evaluation of the flexural strength of rotary files Protaper Gold, 2Shape, V-Taper Fanta Gold - Matumay-Santos, Fabiola del Pilar (2020)
Background: Nickel-titanium rotary files with thermomechanical treatment were developed to allow greater flexibility when instrumenting the root canals. The instruments allowed operators to deal with duct curvatures more easily. Manufacturers are trying to produce files that work better efficiently and safely. Knowing the properties of marketed files is especially important in helping you choose an appropriate file system. The objective of this study was to evaluate the flexibility of three different nickel-titanium (NiTi) files with thermomechanical treatment at two different points along the file. Materials and methods: The flexibility of three NiTi files with thermomechanical treatment (Protaper Gold, 2Shape and V-Taper Fanta Gold) was measured. Each file was clamped at 3 mm and 7 mm (n = 10 / length / file) and a universal testing machine was used to bend the files to a maximum strength. All data were statistically analyzed by one-way analysis of variance and post-hoc Tukey test (P = 0.05) to determine any significant differences. Results: There were statistically significant differences (P <0.05). In general, V-Taper Fanta Gold was the most rigid, Protaper Gold showed the highest values of force and deformation was significantly more flexible. Conclusión: Protaper Gold files showed greater flexibility compared to the other files studied.